ANALISIS PERAN KEPEMIMPINAN CAMAT TERHADAP PEMBINAAN PEGAWAI DI KANTOR CAMAT KECAMATAN TADU RAYA KABUPATEN NAGAN RAYA - Sri Wahyu Handayani (Jurnal Public Policy, 2017)
This article aims to determine the role of sub-district leadership in coaching employees in the Head Office of Tadu and the factors that influence the subdistrict governments to develop employees at Head Office Tadu. This study uses a qualitative method with purposive sampling techniques. The results of the research that leadership role in coaching employees in the Head office of the District Head Tadu Nagan Raya, has been implemented as not it should be. But basically camat is not based on a government education (SSTP), but camat was commissioned by head of district (bupati), so that the role of the sub-district leadership of the coaching employees in the sub-district office Tadu very emproyent the organization goes by. This is evident from the pattern of the services provided by employees and contract workers to the community environment of the Tadu District. Other hand, many factors that affect the role of Head of the coaching employee first because of factors have been determined based on the regulations of the district. Second, the head is obliged to foster employee. Third, the rules that head is responsible for his subordinates. Fifth, head as the initiative itself. Sixth, because of discipline and responsibility of a leader to build employee duties. Seventh,it was also due to his obligations as camat factor in fostering employee, because camat as head of the district. Eighth, due to employee discipline is highly dependent on the leadership style of the subdistrict head, so that the district head and firm discipline the employee will be disciplined. Nine, because of the factor so as to foster employee transferred to the improvement of service quality. Keywords: Analysis, Strategy, Leadership, Head, Fostering Office